Occurrence and removal of antibiotic-resistant bacteria in domestic wastewater / Zummy Dahria Mohamed Basri - Mohamed Basri, Zummy Dahria (2020)
Since its introduction in 1929, antibiotics is extensively used in many fields, including medicine, agriculture and aquaculture. The uncontrolled usage of antibiotics however leads to antibiotic-resistance, a phenomenon where the bacteria become immune to the antibiotics or able to resist antibiotics, resulting in ineffective treatment and new type of antibiotic has to be created. In this study, bacteria with the antibiotic resistance have found a way to wastewater treatment plant, which was proven from the presence of E. coli, Salmonella spp. and Shigella spp. in the secondary effluent of the conventional wastewater treatment plant using the secondary treatment aeration tank, with an average of 2.36 x 104, 2.61 x 104 and 3.42 x 104 CFU/mL, respectively. From the concentration, E. coli, Salmonella spp. and Shigella spp. have shown to be resistant to more than two antibiotics such as erythromycin, amoxicillin, ampicillin, cephalexin, ciprofloxacin, penicillin, cloxacillin, gentamicin, chloramphenicol, and trimethoprimsulfamethoxazole, thus making then multidrug-resistant bacteria, with percentage range 2-100% of resistivity. Based on the results, tertiary treatments using ultraviolet (UV) and titanium dioxide (TiO2) after secondary treatment are recommended to remove antibiotic resistance bacteria. From the tests performed, UV-TiO2 treatments with 252 mJ/cm2 of UV dosage and 1.75 g/L of TiO2 are able to deactivate MDR-E. coli up to 7.7-log removal in UPW and 5.5-log removal in the secondary effluent. The highest MDR-Salmonella spp. inactivation was obtained using similar UV and TiO2 doses, where they deactivate up to 6.0-log removal in UPW and 4.9-log removal in the secondary effluent. Meanwhile, MDR-Shigella spp. was removed using similar UV dose and 1.25 g/L TiO2, up to 7.8-log removal in UPW and 5.4-log removal in the secondary effluent. All MDR-bacteria need to be inactivated before the treated water is released into the water environment because it was also found that the resistant genes found in a bacterium are transferable to other no-resistant bacteria in the system. Wastewater treatment plant causes the risk of antibiotic resistance bacteria in water bodies. Shigella spp. and Salmonella spp. were found to transfer more easily and gain the resistant gene in water environment in comparison to E. coli. The risk of the antibiotic resistance issue to individuals increases with the increase of contact with microorganisms. In this study, the risk analysis of human health shown by DALY indicates that human exposure to the threat of diseases caused by ARB for antibiotic resistant levels of E. coli, Salmonella spp. and Shigella spp. were 7.92 x 10-3, 4.6 x 10- 3 and 1.6 x 10-4, respectively, the values are higher than the permissible limit set by the World Health Organization. Thus, there is high risk of water contamination due to pathogenic antibiotic resistant bacteria that affects humans who are in direct contact with water.